2013
DOI: 10.3727/096368912x654939
|View full text |Cite
|
Sign up to set email alerts
|

Human-Scale Whole-Organ Bioengineering for Liver Transplantation: A Regenerative Medicine Approach

Abstract: At this time, the only definitive treatment of hepatic failure is liver transplantation. However, transplantation has been limited by the severely limited supply of human donor livers. Alternatively, a regenerative medicine approach has been recently proposed in rodents that describe the production of three-dimensional whole-organ scaffolds for assembly of engineered complete organs. In the present study, we describe the decellularization of porcine livers to generate liver constructs at a scale that can be cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
182
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 169 publications
(187 citation statements)
references
References 31 publications
3
182
0
2
Order By: Relevance
“…The results demonstrated that the 3-dimensional DSM scaffold with favorable biocompatibility was suitable for cell engraftment, and facilitated significantly better lineage-specific differentiation in combination with growth factors in vitro, compared to the 2-dimensional TCF culture system. The feasibility of liver reconstruction based on DLM and hepatocytes or stem cells [26][27][28][29] has been demonstrated in rodent, goat and swine, which has stimulated a decellularization upsurge worldwide. The ultimate goal of decellularization is to apply engineered HLT in clinical work.…”
Section: Discussionmentioning
confidence: 99%
“…The results demonstrated that the 3-dimensional DSM scaffold with favorable biocompatibility was suitable for cell engraftment, and facilitated significantly better lineage-specific differentiation in combination with growth factors in vitro, compared to the 2-dimensional TCF culture system. The feasibility of liver reconstruction based on DLM and hepatocytes or stem cells [26][27][28][29] has been demonstrated in rodent, goat and swine, which has stimulated a decellularization upsurge worldwide. The ultimate goal of decellularization is to apply engineered HLT in clinical work.…”
Section: Discussionmentioning
confidence: 99%
“…2 Following the success of perfusion decellularization in the cardiac model, the principle has been applied to other whole organs such as the kidney, [3][4][5][6] lungs, [7][8][9] and liver. 6,[10][11][12][13][14][15][16][17][18] A number of effective strategies for the decellularization of rat livers have been described by Uygun et al, 10 Bao et al 19 and Baptista et al…”
Section: Introductionmentioning
confidence: 99%
“…A popular strategy being developed for the creation of such implantable liver grafts involves the decellularization of whole organs, and subsequent reseeding with relevant cell types, followed by maturation of the neoorgan in a physiologically appropriate bioreactor, and then implantation of these constructs in animals. [232][233][234][235][236][237][238][239][240] Although most studies using this approach have demonstrated feasibility, they have also demonstrated limited survivability and function of the grafts after implantation into animals. These disappointing results have been largely attributed to a failure to maintain a durable vascular network and failure to rebuild the complex liver microarchitecture required for function by the assembled liver graft after transplantation.…”
Section: Clinical Innovation In Transplantationmentioning
confidence: 99%